Sweet potato - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Research scientist Thumbiko Mkandawire discusses hoeing, hand weeding, intercropping and herbicides as methods of weed control in this crop.